Macroeconomic fluctuations in home countries and immigrants' well-being: New evidence from down under - Nguyen, Ha; Duncan, Alan (Curtin University, 2015)
In this paper we provide the first solid empirical evidence that improvements in home countries' macroeconomic conditions, as measured by a higher GDP per capita and lower price levels, increase immigrants' subjective well-being. We demonstrate this using 12 years of data from the Household Income and Labour Dynamics in Australia panel, as well as macroeconomic indicators for 59 countries of origin, and exploiting exogenous changes in macroeconomic conditions across home countries over time. Controlling for immigrants' observable and unobservable characteristics we also find the positive GDP impact is statistically and economically large in size. Furthermore, the GDP and price impact erodes when immigrants get older, or when they stay in the host country beyond a certain period of time. However, home countries' unemployment rates and exchange rate fluctuations have no impact on immigrants' well-being.